KORELASI KARTU MEMBER MATAHARI REWARD OVO (MRO) DENGAN PEMBELANJAAN MENGGUNAKAN METODE APRIORI (STUDI KASUS : PT.MATAHARI DEPARTEMENT STORE BINJAI) - Citra Ayu Wasih; Budi Serasi Ginting; Yani Maulita (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
Matahari Department Store is one of the large companies engaged in retail with fashion products and other style needs. This company every day must meet consumer needs and are required to make the right decisions in determining sales strategies. To be able to do this, companies need sufficient sources of information to be able to analyze further. For example, by utilizing sales transaction data that has been stored in the database, the management can find out customer habits or customer behavior regarding what products are often purchased and the use of Matahari Reword member cards